@@ -40,20 +40,20 @@ module _ (_≈ᴬ_ : Rel {a} A ℓa) (S : Setoid c ℓ) where
40
40
private
41
41
_*ᵣ_ = flip _*ₗ_
42
42
43
- *ₗ-assoc+ comm⇒*ᵣ-assoc :
43
+ *ₗ-assoc∧ comm⇒*ᵣ-assoc :
44
44
L.RightCongruent _≈ᴬ_ _*ₗ_ →
45
45
L.Associative _*_ _*ₗ_ → Commutative _*_ → R.Associative _*_ _*ᵣ_
46
- *ₗ-assoc+ comm⇒*ᵣ-assoc *ₗ-congʳ *ₗ-assoc *-comm m x y = begin
46
+ *ₗ-assoc∧ comm⇒*ᵣ-assoc *ₗ-congʳ *ₗ-assoc *-comm m x y = begin
47
47
(m *ᵣ x) *ᵣ y ≈⟨ refl ⟩
48
48
y *ₗ (x *ₗ m) ≈⟨ *ₗ-assoc _ _ _ ⟨
49
49
(y * x) *ₗ m ≈⟨ *ₗ-congʳ (*-comm y x) ⟩
50
50
(x * y) *ₗ m ≈⟨ refl ⟩
51
51
m *ᵣ (x * y) ∎
52
52
53
- *ₗ-assoc+ comm⇒*ₗ-*ᵣ-assoc :
53
+ *ₗ-assoc∧ comm⇒*ₗ-*ᵣ-assoc :
54
54
L.RightCongruent _≈ᴬ_ _*ₗ_ →
55
55
L.Associative _*_ _*ₗ_ → Commutative _*_ → B.Associative _*ₗ_ _*ᵣ_
56
- *ₗ-assoc+ comm⇒*ₗ-*ᵣ-assoc *ₗ-congʳ *ₗ-assoc *-comm x m y = begin
56
+ *ₗ-assoc∧ comm⇒*ₗ-*ᵣ-assoc *ₗ-congʳ *ₗ-assoc *-comm x m y = begin
57
57
((x *ₗ m) *ᵣ y) ≈⟨ refl ⟩
58
58
(y *ₗ (x *ₗ m)) ≈⟨ *ₗ-assoc _ _ _ ⟨
59
59
((y * x) *ₗ m) ≈⟨ *ₗ-congʳ (*-comm y x) ⟩
@@ -66,23 +66,56 @@ module _ (_≈ᴬ_ : Rel {a} A ℓa) (S : Setoid c ℓ) where
66
66
private
67
67
_*ₗ_ = flip _*ᵣ_
68
68
69
- *ᵣ-assoc+ comm⇒*ₗ-assoc :
69
+ *ᵣ-assoc∧ comm⇒*ₗ-assoc :
70
70
R.LeftCongruent _≈ᴬ_ _*ᵣ_ →
71
71
R.Associative _*_ _*ᵣ_ → Commutative _*_ → L.Associative _*_ _*ₗ_
72
- *ᵣ-assoc+ comm⇒*ₗ-assoc *ᵣ-congˡ *ᵣ-assoc *-comm x y m = begin
72
+ *ᵣ-assoc∧ comm⇒*ₗ-assoc *ᵣ-congˡ *ᵣ-assoc *-comm x y m = begin
73
73
((x * y) *ₗ m) ≈⟨ refl ⟩
74
74
(m *ᵣ (x * y)) ≈⟨ *ᵣ-congˡ (*-comm x y) ⟩
75
75
(m *ᵣ (y * x)) ≈⟨ *ᵣ-assoc _ _ _ ⟨
76
76
((m *ᵣ y) *ᵣ x) ≈⟨ refl ⟩
77
77
(x *ₗ (y *ₗ m)) ∎
78
78
79
- *ᵣ-assoc+ comm⇒*ₗ-*ᵣ-assoc :
79
+ *ᵣ-assoc∧ comm⇒*ₗ-*ᵣ-assoc :
80
80
R.LeftCongruent _≈ᴬ_ _*ᵣ_ →
81
81
R.Associative _*_ _*ᵣ_ → Commutative _*_ → B.Associative _*ₗ_ _*ᵣ_
82
- *ᵣ-assoc+ comm⇒*ₗ-*ᵣ-assoc *ᵣ-congˡ *ᵣ-assoc *-comm x m y = begin
82
+ *ᵣ-assoc∧ comm⇒*ₗ-*ᵣ-assoc *ᵣ-congˡ *ᵣ-assoc *-comm x m y = begin
83
83
((x *ₗ m) *ᵣ y) ≈⟨ refl ⟩
84
84
((m *ᵣ x) *ᵣ y) ≈⟨ *ᵣ-assoc _ _ _ ⟩
85
85
(m *ᵣ (x * y)) ≈⟨ *ᵣ-congˡ (*-comm x y) ⟩
86
86
(m *ᵣ (y * x)) ≈⟨ *ᵣ-assoc _ _ _ ⟨
87
87
((m *ᵣ y) *ᵣ x) ≈⟨ refl ⟩
88
88
(x *ₗ (m *ᵣ y)) ∎
89
+
90
+
91
+ ------------------------------------------------------------------------
92
+ -- DEPRECATED NAMES
93
+ ------------------------------------------------------------------------
94
+ -- Please use the new names as continuing support for the old names is
95
+ -- not guaranteed.
96
+
97
+ -- Version 2.3
98
+
99
+ *ₗ-assoc+comm⇒*ᵣ-assoc = *ₗ-assoc∧comm⇒*ᵣ-assoc
100
+ {-# WARNING_ON_USAGE *ₗ-assoc+comm⇒*ᵣ-assoc
101
+ "Warning: *ₗ-assoc+comm⇒*ᵣ-assoc was deprecated in v2.3.
102
+ Please use *ₗ-assoc∧comm⇒*ᵣ-assoc instead."
103
+ #-}
104
+
105
+ *ₗ-assoc+comm⇒*ₗ-*ᵣ-assoc = *ₗ-assoc∧comm⇒*ₗ-*ᵣ-assoc
106
+ {-# WARNING_ON_USAGE *ₗ-assoc+comm⇒*ₗ-*ᵣ-assoc
107
+ "Warning: *ₗ-assoc+comm⇒*ₗ-*ᵣ-assoc was deprecated in v2.3.
108
+ Please use *ₗ-assoc∧comm⇒*ₗ-*ᵣ-assoc instead."
109
+ #-}
110
+
111
+ *ᵣ-assoc+comm⇒*ₗ-assoc = *ᵣ-assoc∧comm⇒*ₗ-assoc
112
+ {-# WARNING_ON_USAGE *ᵣ-assoc+comm⇒*ₗ-assoc
113
+ "Warning: *ᵣ-assoc+comm⇒*ₗ-assoc was deprecated in v2.3.
114
+ Please use *ᵣ-assoc∧comm⇒*ₗ-assoc instead."
115
+ #-}
116
+
117
+ *ᵣ-assoc+comm⇒*ₗ-*ᵣ-assoc = *ᵣ-assoc∧comm⇒*ₗ-*ᵣ-assoc
118
+ {-# WARNING_ON_USAGE *ᵣ-assoc+comm⇒*ₗ-*ᵣ-assoc
119
+ "Warning: *ᵣ-assoc+comm⇒*ₗ-*ᵣ-assoc was deprecated in v2.3.
120
+ Please use *ᵣ-assoc∧comm⇒*ₗ-*ᵣ-assoc instead."
121
+ #-}
0 commit comments